Inventory Management of Health Commodities in a Tertiary Teaching Hospital in Ethiopia - Legese, Nanati; Teshome, Dawit; Gedif, Teferi (Frontiers in Pharmacology, 2022)
Background: Analyzing purchased health commodities based on their budgetary consumption and importance is crucial for efficient utilization of a hospital’s budget. However, it is rarely seen when hospitals, mostly in developing countries, conduct such kinds of analyses and make an informed decision, including to utilize their limited budget efficiently. Therefore, the purpose of this study was to analyze a 3-year inventory of health commodities (medicines, medical supplies, and laboratory reagents and chemicals) in Saint Paul Hospital Millennium Medical College (SPHMMC). Methodology: The study was conducted in SPHMMC located in Addis Ababa, Ethiopia. It is one of the largest specialized public hospitals in the country. It is a huge teaching hospital in the country where a large amount of budget is utilized. Three years of data were collected and ABC, VEN, and ABC-VEN matrix techniques were applied for the analysis. The data collection period was from March to April 2017. Results: An average of 296 medicines, 194 laboratory commodities, and 105 medical supplies were purchased over 3 years. Class A medicines, which consume 80% of the total annual pharmaceutical expenditures (APE) account, are 17.8%–20% of the total medicines by quantity. Antibiotics (ceftriaxone 1 gm injection and metronidazole), IV fluids (sodium chloride 0.9% injection and dextrose 40% injection), and antidiabetic medication (insulin zin suspension and metformin) are among the top 10 medications by value that consume significant amounts of the budget of the hospital. On VEN analysis, an average of 24% of the items were vital, 67% were essential, and 4–8–8.9% were nonessential. Nonessential items consumed 0.49%, 9.9%, and 1.1% of Annual Expenditures (AEs) in 2013/14, 2014/15 and 2015/16, respectively. On ABC-VEN matrix analysis, a single expensive and nonessential medicine (valganciclovir HCL 450 mg tablet) consumed 9.4% of expenditure in 2014/15. Class A laboratory commodities, which consume 70%–80% of the total laboratory expenditures represented 8.5%–20% of the total laboratory commodities analyzed for the 3 years. From class A items, antimonoclonal antibodies in 2013/14, hemocue glucose 201 4 × 25 tests in 2014/15, and glucose tests in 2015/16 consumed the highest percentages: 9.2%, 8.2%, and 23.7% of the AEs, respectively. There were laboratory commodities procured out of the VEN list, and these accounted for 6.8%–31.2% of the total laboratory expenditures over the 3 years. Class A medical supplies, which consumed 80% of the total medical supply expenditures, represented only 8.2%–15.8% of the total items over the 3 years studied. Surgical gauze 90 cm × 100 m, surgical gloves sterile latex number 7.5, and examination gloves were the top three based on expenditures in all the studied years. In 2015/16, examination gloves alone consumed 71.9% of the total expenditure. Conclusion: SPHMMC manages large numbers of health commodities (more than 500 excluding program commodities) which necessitate efficient inventory management practice in place. However, the purchase of the commodities particularly those products used for laboratory diagnosis is not strictly based on the hospital’s VEN list, indicating the need for better communication of the laboratory unit with the Drug and Therapeutic Committee (DTC) of the hospital. The DTC of the hospital should update the VEN list of the health commodities and strictly enforce the hospital procurement to adhere to the agreed upon list of medicines. In addition, the hospital should prioritize and decide the quantity and frequency of ordering health commodities based on regular ABC-VEN results.